Noteworthy records from the eastern andean slopes of northern Ecuador: Registros notables de la vertiente oriental de los Andes del norte de Ecuador (Ornitología Colombiana, 2021)
New occurrence sites for two neartic/neotropical migrants and altitudinal extensions for five resident species in the Ecuadorian eastern Andean foothills are reported, based on our field observations along an altitudinal range from 600 to 1600 m elevation within three localities along the Ecuador-Perú East Andes Endemic Bird Area (EBA). Gathering species occurrence data will aid us to better understand the effects that changes in land use have on resident birds’ movement patterns and distribution as well as elucidate wintering distribution for migrant ones.